Why most people with mental illness go untreated? economic perspectives and evidence from China - Xuezheng, Qin; Chee-Ruey, Hsieh (University of Nottingham, 2017)
Due to the rapid economic growth and advancement in medical technology, many countries have experienced in the past decades an epidemiological transition from communicable to non- communicable dieses (NCDs). One of the challenges in the era of NCDs is the large treatment gap, measured by the difference between the need for treatment and the actual provision of treatment, among patients with NCDs. This paper investigates the causes of treatment gap in mental healthcare from the perspective of economics. Specifically, we hypothesizes that people with mental illness face four major hurdles in seeking appropriate healthcare, namely the high nonmonetary cost due to stigma, the high out-of-pocket payment due to insufficient public funds devoted to the mental health sector, the high time prices due to low mental healthcare resource availability, and the low treatment benefit due to slow technology diffusion. We then use China as a study setting to show the country-specific evidence. Our analysis supports the above theoretical argument on the four access barriers, which in turn sheds light on the effective approaches to mitigate the treatment gap. Four policy options are then discussed, including an information campaign for mental health awareness, increasing public investment in primary mental healthcare resources, transforming the healthcare system towards an integrated people-centered system and capitalizing on e-health technologies.